Implementasi Peraturan Daerah Nomor 14 Tahun 2020 tentang Pengelolaan Sampah Rumah Tangga dan Sampah Sejenis Sampah Rumah Tangga di Tempat Pembuangan Sampah Kabupaten Gunungkidul - Herlambang, Ary Wisnu; Djaja, Djuniawan Karna; Manik, Rusman Rupinus (Tumoutou Social Science Journal, 2024)
This study aims to analyze the implementation of Regional Regulation No. 14 of 2020 on Household Waste Management at TPS 3R Ngawu Asri, Kalurahan Ngawu, Kapanewon Playen, Gunungkidul Regency. The background of this research is the increasing volume of waste due to population growth, which demands a paradigm shift in waste management from disposal to managing waste through the 3R concept (Reduce, Reuse, Recycle). This study used a qualitative method with a descriptive approach, collecting data through interviews, observations, and documentation from various primary and secondary sources. The results show that the policy implementation has not been optimal, viewed from aspects of communication, resources, disposition, and bureaucratic structure. The main inhibiting factors are the lack of human resources, facilities, and adequate vehicle support. However, there is support from the Environmental Service through training and technical guidance. In conclusion, despite efforts being made, waste management at TPS 3R Ngawu Asri still requires improvement in resources and coordination.